Diplomatic journey - "Kapur, Harish" (New Delhi, 2004)
In his new book, 'Diplomatic Journey: Emerging India, Prof. Harish Kapur deals with the totality of India's Foreign Policy since its independence in 1947. The focus of the book is on how India's Foreign policy is determined, what are its permanent features and who decides its framework. It is divided in three parts. Part I is devoted to an analysis of the environmental factors that influence India's foreign policy. Part II conceptualizes India's foreign policy goals the goals of security of modernization of regional hegemony and of international role playing. Part III deals with decision making process. First of all the author deals with the different institutions that are concerned with foreign policy, and has evaluated their role and their impact.
Keywords: Foreign relations - India